Improving Teacher Quality in the Perspective of Islamic Teaching Professionalism - Rudi Ahmad Suryadi (ISTAWA, 2021)
Various components influence quality religious education. One of the dominant ones is the teacher. Learning will be of high quality if the teacher is competent and professional. The professional development of teachers is a stage in strengthening skills, competencies, and career advancement, which leads to an increase in the quality of learning being taught. This research uses a literature study method. Sources of data obtained through references and other reading sources related to teacher professionalism, the results showed that the problem of teacher professionalism originated from three components, namely self-development, scientific publications, and innovative work. Quality improvement is more dominantly influenced by teacher professionalism, where teachers are required to achieve predetermined qualifications. by meeting adequate qualifications, the teacher's position will automatically increase. Professional development is related to advancing knowledge and skills by considering attitudes and approaches to improving the quality of learning. It is a process of growing teacher professionalism in strengthening the skills, duties and careers of teachers in facing the changes that occur.Pendidikan agama yang bermutu dipengaruhi oleh berbagai komponen. Salah satunya yang dominan adalah guru. Pembelajaran akan bermutu, apabila gurunya kompeten dan profesional. Pengembangan profesionalitas guru merupakan tahapan dalam penguatan keahlian, kompetensi, dan peningkatan karir yang berujung pada peningkatan mutu pembelajaran yang diampu. Riset ini menggunakan metode studi kepustakaan, sumber data diperoleh melalui referensi dan sumber bacaan lain yang berkaitan dengan profesionalisme guru.  Hasil penelitian menunjukkan bahwa masalah profesioalisme guru berawal dari tiga komponen, yaitu pengembangan diri, publikasi ilmiah, dan karya inovatif. Peningkatan kualitas lebih dominan dipengaruhi oleh profesionalisme guru, dimana guru dituntut untuk mencapai kualifikasi yang telah ditetapkan. dengan memenuhi kualifikasi yang memadai maka posisi guru akan secara otomatis meningkat. Pengembangan profesionalisme terkait dengan peningkatan pengetahuan dan keterampilan dengan mempertimbangkan sikap dan pendekatan untuk meningkatkan kualitas pembelajaran. Merupakan proses peningkatan profesionalisme guru dalam memperkuat keterampilan, tugas dan karir guru dalam menghadapi perubahan yang terjadi.